PENGARUH KARAKTERISTIK KEWIRAUSAHAAN DAN KNOWLEDGE MANAGEMENT TERHADAP PENGEMBANGAN USAHA (Studi Kasus Pada Sentra Industri Tempe di Kelurahan Krobokan Kota Semarang) - Jenita Adinda Bangun; Agung Budiatmo (Universitas Diponegoro, 2018)
This research’s goal to explain the influence of entrepreneurship characteristics and knowledge management toward development of enterprise in center of Tempe’s Industries in Krobokan Village Semarang City. The research’s type is explanatory research, with with its nonprobability sampling of sample technique. Sample in this 35 respondent that constitutes of entrepreneurs in center of Tempe’s Industries in Krobokan Village Semarang City. Data’s collection technique used in this research are interview and questionnaire (data collection instrument). Data analysist technique uses quantitative analysist technique that are validity test, reliability test, classic assumption test, cross tab, simple linear regression, multiple linear regression, t-test and F-test with SPSS 20.0. Research findings show that variable of entrepreneurship characteristic has strong enough influence toward variable of enterprise’s development that is 20,2%, variable of knowledge management has strong enough influence that is 28,9%, whereas simultaneously entrepreneurship characteristic variable and knowledge management variable has strong enough influence 33,5% toward of enterprise development. It does mean that as entrepreneurship characteristic and knowledge management, therefore development of enterprise in center Tempe’s Industries Krobokan Village will get better. Knowledge management toward enterprise’s development has greater influence instead of entrepreneurship characteristic variable. Based on the result of the research, the researcher suggested that center Tempe’s Industries Krobokan Village has different ideas and creative to innovate the product that has been produced and able to manage the existing knowledge to create new knowledge, thus the development of the undertaken will develop well accordingly with desirable expectations.